Kepastian Hukum Penggunaan Artificial Intelegence Terhadap Penyimpanan Protokol Notaris - Himami, Desyana; Sari, Nuzulia Kumala; Ali, Moh. (PT Matra Cendikia Abadi, 2025)
Legal uncertainty related to the use of artificial intelligence (AI) in storing notary protocols, which is part of the implementation of the cyber notary concept in Indonesia. The background of this research is the era of the Industrial Revolution 4.0 and Society 5.0, which demands high efficiency, security, and accessibility in storing notary documents, especially to reduce the risk of damage to physical documents due to natural disasters and other factors. Although the use of AI in storing notary protocols promises better efficiency and security, there is no legal certainty that supports this application, due to the overlap and inconsistency between the Notary Law and the Information and Electronic Transactions Law. This study uses a normative legal methodology with a statutory and conceptual approach to analyze related legal regulations and explore issues that arise due to the legal vacuum in the use of AI by notaries. The results of the study show notaries have an obligation to make minutes of deeds and archive them as a form of action from the notary protocol. The obligation to store these minutes of deeds aims to maintain the authenticity of the deed. Storage of notary protocols until now still uses printed media stored in a separate archive room at the Notary's office, this certainly poses a high risk to the safety of the notary protocol if there is force majeure at the Notary's Office. Storage of Notary protocols using AI does not guarantee legal certainty, because there are no comprehensive and explicit regulations regarding the use of AI in Storing Notary protocols. However, this is a challenge whose implementation requires more specific implementing regulations so that notaries have clear guidelines in carrying out the document digitization process safely and legally.